Preparation method of high-strength and high-toughness lead-tin bronze bar
Through preheating treatment and cone-ported sleeve extrusion technology, combined with electrical pulse or solid solution heat treatment, the thermal brittleness problem of lead-tin bronze alloy during the hot extrusion process is solved, and its mechanical properties are significantly improved, meeting the service performance requirements of the rotor bushing of high-pressure plunger pumps for aviation.
Patent Information
- Application Number
- CN202510614860.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2045-05-14
AI Technical Summary
Lead-tin bronze alloys have thermal brittleness problems during the hot extrusion process, resulting in the bars being easily fragile, and the distribution of lead particles is difficult to control, and performance improvement is limited.
Preheating treatment is used to regulate the distribution of lead particles, and the tapered mold cover extrusion technology is used to improve the thermal processing process of the alloy. Combined with electrical pulses or solid solution heat treatment, microstructure distribution is regulated to improve mechanical properties.
Through this method, the thermal brittleness problem during the hot extrusion process was successfully suppressed, and the high strength and high plastic toughness of lead-tin bronze alloys were achieved, meeting the demanding service environment needs in the aviation field.
Smart Images

Figure CN120138426A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lead-tin bronze bar processing, and particularly relates to a preparation method of a high-strength and high-toughness lead-tin bronze bar. Background Art
[0002] The rotor of the high-pressure plunger pump for aviation is one of the most important parts in the aircraft hydraulic system, and its performance and quality determine the transmission efficiency and service life of the high-pressure plunger pump. The inner lining of the high-pressure plunger pump rotor is wear-resistant lead-tin bronze. The presence of lead endows the alloy with excellent self-lubricity, effectively reducing the friction and wear performance, while improving the wear resistance and fatigue resistance of the material. At the same time, the soft particles of lead can disperse the stress concentration and reduce the formation of fatigue cracks. Therefore, compared with other copper alloys, lead-tin bronze has higher mechanical strength, wear resistance, self-lubricity and corrosion resistance, and is suitable for more demanding service environments, and is the core material of high-end pump bodies.
[0003] At present, the preparation method of lead-tin bronze is the casting method. As a multi-element high-solute copper alloy, lead in lead-tin bronze is insoluble in copper, and the solid solubility of tin in copper at room temperature is only 0.5 wt.%. There are defects such as lead particle aggregation, tin-rich phase segregation and microcracks in the as-cast structure of the alloy, resulting in its mechanical properties being difficult to meet the requirements of high-speed and heavy-duty service conditions. At the same time, lead-tin bronze has a significant volume shrinkage during solidification, and there are more shrinkage cavities and porosity in the casting, reducing the strength, durability and overall stability of the casting.
[0004] In summary, there are many defects such as lead particle aggregation, tin-rich phase segregation and microcracks in the as-cast lead-tin bronze, resulting in its strength and wear resistance being unable to meet the service requirements of high-speed and heavy-duty, which has become a bottleneck problem restricting the improvement of the service performance of the rotor bushing of the high-pressure plunger pump for aviation.
[0005] At present, there have been many reports on the research of improving the mechanical properties of as-cast multi-element copper alloys: The patent "202011073090.9" describes a hot extrusion forming method for copper alloy tracks, and the steps are as follows: ⑴ Blank processing: ① Saw cut the forged bright blank round steel; ② Drill a hole in the center of the blank; ③ Turn and polish the outer surface and the head; ⑵ Blank heating: The heating temperature is 900 - 950 °C; ⑶ Tool and die preparation: Use extrusion dies with the same shape; ⑷ Lubrication: Apply lubricant to the extrusion die, manipulator, and extrusion cylinder; ⑸ Hot extrusion: Hot extrude the blank into shape; ⑹ Cooling: Cool the copper alloy track to room temperature; ⑺ Solution heat treatment: The heating temperature is 930 - 950 °C; ⑻ Inspection: Inspect the hardness and conductivity; ⑼ Straightening: Straighten the copper alloy track; ⑽ Cold drawing: Cold draw the copper alloy track; ⑾ Aging heat treatment; ⑿ Inspect the cross-sectional hardness, conductivity, and room temperature tensile strength; ⒀ Straightening. Through optimizing the die design and the extrusion forming process, the present invention ensures that the workpiece is formed in one time, the produced copper alloy track has good surface quality, and the physical, chemical, and mechanical properties of the product are improved.
[0006] The patent "202010801676.6" reports a semi-solid backward extrusion method for bushing parts, belonging to the field of semi-solid forming. The method of the present invention is as follows: Heat the semi-solid blank obtained by the alloy material through the SIMA method to a temperature above the solidus temperature and keep it warm, then put it into a preheated die for backward extrusion forming and pressure holding, perform water quenching on the parts after backward extrusion, and finally perform short-time solution + aging heat treatment. The method of the present invention adopts the semi-solid backward extrusion forming method, which has high production efficiency, low energy consumption, high product quality, high material utilization rate, and is easy to realize mechanized and automated production.
[0007] In summary, hot extrusion can improve the microstructure of copper alloy and significantly improve its mechanical properties. However, the addition of lead particles in lead-tin bronze makes lead-tin bronze different from other copper alloys. On the one hand, lead is a low melting point phase, the melting point of lead is 327.5 °C, while the hot extrusion temperature of copper alloy needs to be carried out between 600 °C and 900 °C. The huge temperature difference makes it difficult to solve the hot brittleness of the lead-containing alloy during the hot extrusion process. The lead-tin bronze bar is extremely easy to break during the extrusion process, and the distribution of lead particles is difficult to control, resulting in limited performance improvement. On the other hand, the solid solubility of tin in copper at room temperature is extremely limited. There are a large number of tin-rich phases in the microstructure of lead-tin bronze after hot extrusion, deteriorating the plastic toughness of the alloy and making it difficult to meet the performance requirements of wear-resistant lead-tin bronze in the harsh service environment of the aviation field. Therefore, how to further post-treat to strengthen the alloy performance is particularly important. Summary of the Invention
[0008] To solve the above problems, the present invention provides a method for preparing a high-strength and high-toughness lead-tin bronze bar. This method uses the method of "preheat treatment to control the distribution pattern of lead particles + extrusion with a tapered die jacket" to improve the plasticity during the hot extrusion of lead-tin bronze, smoothly realizing the hot extrusion forming of lead-tin bronze, and improving the mechanical properties of the alloy by refining the grain size and controlling the distribution pattern of lead particles. Further, the extruded bar is subjected to current pulse heat treatment to control the content and distribution of the tin-rich phase in the extruded bar, and finally a high-performance lead-tin bronze alloy bar is obtained.
[0009] A method for preparing a high-strength and high-toughness lead-tin bronze bar according to the present invention includes the following steps: Step 1: According to the weight percentage, heat the metal materials of 2.0%-3.25% lead, 7.0%-11.0% tin, 3.0%-4.0% nickel, and the rest being copper to a liquid state, pour them into a water-cooled copper mold and start the water-cooling cycle. After cooling, take them out to obtain a as-cast lead-tin bronze alloy. Step 2: Use electrolytic purple copper with a purity of 99.9% for machining to make a copper jacket with a blind hole, assemble the as-cast lead-tin bronze obtained in the previous step into the blind hole of the copper jacket, and seal the open end of the blind hole of the assembled copper jacket to form an integral combined blank body. Step 3: Anneal the assembled combined blank body at 270°C - 330°C for 25 min - 35 min and apply a glass lubricant, then air-cool to 50°C - 100°C. Step 4: Preheat the tapered extrusion die with a taper of 67° - 70°, a depth of 30 mm - 35 mm, and a diameter of 20 mm at 380°C - 400°C for a preheating duration of 0.5 h - 1 h. After the preheating is completed, spray a cubic boron nitride release agent spray on the die. Step 5: Place the combined blank body in a muffle furnace and heat it from 350°C - 400°C to 600°C - 800°C at a heating rate of 5°C - 10°C per minute, and hold for 30 min - 45 min. Step 6: Place the combined blank body heated in Step 5 in the tapered die for hot extrusion. The hot extrusion temperature is 650°C - 800°C, and quench the extruded combined blank body to obtain an extruded sample. Step 7: Heat-treat the extruded sample obtained in Step 6 to obtain a high-quality lead-tin bronze bar that meets the standards.
[0010] Preferably, the extrusion ratio of the hot extrusion process is 9:1, and the extrusion speed is 5 mm / s - 10 mm / s.
[0011] Preferably, the extruded sample is subjected to heat treatment, which is electro-pulse treatment. The voltage of the electro-pulse is set to 50V - 100V, the treatment time is 35s - 40s, the frequency range is 350Hz - 500Hz, and after the electro-pulse treatment, it is cooled to room temperature.
[0012] Preferably, the extruded sample is subjected to heat treatment, which is solution treatment. The extruded sample is heated at 650°C - 750°C for 1h - 2h and then air-cooled to room temperature.
[0013] The present invention proposes to place the as-cast lead-tin bronze in a blind-hole copper sleeve, with the copper in direct contact with the mold, reducing the surface cracking problem caused by the contact friction between the lead-tin bronze and the mold. At the same time, through a pre-treatment of holding at 380°C - 400°C for 0.5h - 1h, the wetting angle between α-Cu and lead particles in the lead-tin bronze is regulated, improving the hot brittleness problem during the hot working process of the alloy and suppressing the cracking problem during the extrusion deformation process, ultimately obtaining a bar with no crack defects on the surface and in the core.
[0014] The present invention uses electro-pulse treatment to regulate the microstructure distribution of the bar after hot extrusion. The electro-pulse treatment has both electrical and thermal effects. By the way of internal heating, it can significantly reduce the volume fraction of the tin-rich phase in the alloy, promote the recrystallization of α-Cu and the dispersion distribution of lead particles. At the same time, compared with other heat treatment methods, the electro-pulse treatment time is shorter, the grain growth effect is suppressed, and the strength and plastic toughness of the alloy can be further improved.
[0015] The present invention uses solution treatment to regulate the microstructure distribution of the bar after hot extrusion. During the solution treatment, the tin-rich phase dissolves back, the α-Cu matrix recrystallizes and the grains grow, and the lead particles are redispersed in the α-Cu matrix structure, which helps to further improve the strength and plastic toughness of the alloy. Description of the Drawings
[0016] Figure 1 It is a schematic diagram of the as-cast structure of the alloy in Example 1.
[0017] Figure 2 It is a schematic diagram of the microstructure of the extruded sample in Example 2.
[0018] Figure 3 It is a schematic diagram of the microstructure after electro-pulse treatment in Example 1.
[0019] Figure 4 It is a schematic diagram of the microstructure of the extruded sample in Example 2 after solution treatment. Detailed Embodiments
[0020] A method for preparing a high-strength and high-toughness lead-tin bronze bar according to the present invention includes the following steps: Step 1: A metal material containing 2.0%-3.25% lead, 7.0%-11.0% tin, 3.0%-4.0% nickel, and the remaining component being copper by weight percentage is heated to a liquid state, then poured into a water-cooled copper mold and the water-cooling cycle is started. After cooling, it is taken out to obtain a as-cast lead-tin bronze alloy; Step 2: Electrolytic purple copper with a purity of 99.9% is machined to produce a copper jacket with blind holes. The as-cast lead-tin bronze alloy obtained in the previous step is assembled into the blind holes of the copper jacket, and the open end of the blind hole of the assembled copper jacket is sealed to form an integral combined blank body; Step 3: The assembled combined blank body is annealed at 270°C - 330°C for 25 min - 35 min and coated with a glass lubricant, then air-cooled to 50°C - 100°C; Step 4: A taper extrusion die with a taper of 67° - 70°, a depth of 30 mm - 35 mm, and a diameter of 20 mm is preheated at 380°C - 400°C for a preheating duration of 0.5 h - 1 h. After the preheating is completed, cubic boron nitride release agent spray is sprayed on the die; Step 5: The combined blank body is placed in a muffle furnace and heated from 350°C - 400°C to 600°C - 800°C at a heating rate of 5°C - 10°C per minute, and held for 30 min - 45 min; Step 6: The combined blank body heated in Step 5 is placed in the taper die for hot extrusion. The hot extrusion temperature is 650°C - 800°C, and the extruded combined blank is quenched to obtain an extruded sample; Step 7: The extruded sample obtained in Step 6 is heat-treated to obtain a high-quality lead-tin bronze rod meeting the standards.
[0021] In one embodiment, the extrusion ratio of the hot extrusion process is 9:1, and the extrusion speed is 5 mm / s - 10 mm / s.
[0022] In one embodiment, the extruded sample is heat-treated, and this heat treatment is an electric pulse treatment. The voltage of the electric pulse is set to 50 V - 100 V, the treatment time is 35 s - 40 s, the frequency range is 350 Hz - 500 Hz, and after the electric pulse treatment is completed, it is cooled to room temperature.
[0023] In one embodiment, the extruded sample is heat-treated, and this heat treatment is a solution treatment. The extruded sample is held at 650°C - 750°C for 1 h - 2 h and then air-cooled to room temperature.
[0024] Example 1: A method for preparing a high-strength and high-toughness lead-tin bronze rod according to the present invention includes the following steps: Step 1: An alloy containing 2.3% lead, 7.79% tin, 4.0% nickel, and the remaining component being copper is heated to a liquid state by weight percentage, then poured into a water-cooled copper mold and the water-cooling cycle is started. After cooling, it is taken out to obtain a as-cast rod-shaped lead-tin bronze alloy; Step 2: Electrolytic tough pitch copper with a purity of 99.9% is machined to produce a copper jacket with a blind hole having a bottom thickness of 20 mm and an inner diameter of 45 mm. The as-cast rod-shaped lead-tin bronze alloy obtained in the previous step is machined to a diameter of 45 mm and assembled in the blind hole of the copper jacket. The open end of the blind hole of the assembled copper jacket is subjected to vacuum sealing welding to form an integral combined blank body; Step 3: The combined blank body is annealed at 300 °C for 25 min and then coated with a glass lubricant, and then air-cooled to 50 °C; The annealing temperature can preferably be 300 °C. The purpose is to regulate the tissue composition of the lead-tin bronze and ensure the extrusion quality. By pre-treating the lead-tin bronze at 300 °C, the proportion of the (α + β) / β phase is increased, and at the same time, the distribution of lead particles in the lead-tin bronze is regulated to ensure that the lead particles are evenly dispersed in the matrix in a spherical shape, ensuring the quality of the subsequent processed products; The purpose of coating the glass lubricant is to reduce the heat generated by friction, thereby preventing local overheating during the extrusion process and reducing the deterioration of material properties caused by overheating. It ensures the surface quality of the hot-extruded product. And in a high-temperature environment, metal materials are prone to oxidation reactions. The lubricant can act as an isolation layer to reduce the contact between the metal and air and prevent the oxidation phenomenon on the material surface; Step 4: A tapered die with a taper of 67°, a depth of 35 mm, and a diameter of 20 mm is preheated at 400 °C for 1 h, and a cubic boron nitride release agent spray is applied; Compared with flat die extrusion, tapered die extrusion can significantly reduce stress concentration and improve the processing plasticity of the alloy; Step 5: The combined blank body is placed in a muffle furnace and heated from 400 °C to 750 °C at a heating rate of 7 °C per minute and held for 45 min; Step 6: The combined blank body heated in Step 5 is placed in the tapered die for a hot extrusion process. The hot extrusion temperature is 750 °C, and the extruded combined blank is quenched to obtain an extruded sample; The extrusion process parameters are determined as follows: Conduct hot simulation compression experiments on lead-tin bronze alloy. The experimental temperature is 600°C - 800°C, and the strain rate is 0.01 - 10. Based on the obtained stress-strain curves, establish the Arrhenius model and the Arvaim model. Combine the geometric model and boundary conditions, i.e., the heat transfer coefficient of the environment is 50 w / m²·k, and the friction ratio factor is 0.4, to establish an extrusion finite element model. Study the processes with extrusion temperatures in the range of 600°C - 800°C, extrusion speeds of 0.01 - 10, and extrusion ratios of 4:1, 9:1, and 16:1 respectively, to obtain the strain distribution law, temperature distribution law, and recrystallized volume fraction distribution law. The optimal extrusion parameters are determined as: extrusion temperature 750°C, extrusion ratio 9:1, and extrusion speed 10 mm / s; Step 7: Electrically pulse the extruded sample in Step 6. Specifically, set the voltage of the electric pulse to 65 V, the processing time to 35 s, and the frequency to 350 Hz. After the electrical pulse treatment is completed, cool it to room temperature to obtain high-quality lead-tin bronze bars that meet the standards; The test results show that the tensile strength of the alloy after electrical pulse treatment reaches 450.7 MPa, and the elongation rate reaches 28.9%, fully meeting the performance standards specified in the Specification for Copper Alloy Die Castings for Aeronautical Use HB - 2002 of the Aviation Industry Standard of the People's Republic of China: the tensile strength is greater than 238 MPa, and the elongation rate is greater than 5%.
[0025] Example 2, A method for preparing a high-strength and high-toughness lead-tin bronze bar of the present invention includes the following steps: Step 1: Heat an alloy containing 2.3% lead, 7.79% tin, 4.0% nickel, and the remaining component being copper to a liquid state by weight percentage, pour it into a water-cooled copper mold, turn on the water-cooling cycle, and take it out after cooling to obtain a cast rod-shaped lead-tin bronze alloy; Step 2: Use electrolytic purple copper with a purity of 99.9% for machining to make a copper sleeve with a blind hole having a bottom thickness of 20 mm and an inner diameter of 45 mm. Machine the cast rod-shaped lead-tin bronze alloy obtained in the previous step to a diameter of 45 mm and assemble it in the blind hole of the copper sleeve. Perform vacuum sealing welding on the open end of the blind hole of the assembled copper sleeve to form an integral combined blank body; Step 3: Anneal the combined blank body at 300°C for 25 min, apply glass lubricant, and then air-cool it to 50°C; The annealing temperature can preferably be 300°C. Its purpose is to regulate the tissue composition of lead-tin bronze and ensure the extrusion quality. By pre-treating lead-tin bronze at 300°C, the proportion of (α + β) / β phase is increased, and at the same time, the distribution of lead particles in lead-tin bronze is regulated to ensure that the lead particles are evenly dispersed in a spherical shape in the matrix, ensuring the quality of the subsequent processed products; The purpose of applying glass lubricant is to reduce the heat generated by friction, thereby preventing excessive local temperature during the extrusion process and reducing the deterioration of material properties caused by overheating. This ensures the surface quality of the hot-extruded products. Moreover, in a high-temperature environment, metal materials are prone to oxidation reactions. The lubricant can serve as an isolation layer to reduce the contact between the metal and air and prevent the oxidation of the material surface; Step 4: Preheat a tapered die with a taper of 67°, a depth of 35 mm, and a diameter of 20 mm at 400 °C for 1 h, and spray cubic boron nitride release agent spray; Compared with flat die extrusion, tapered die extrusion can significantly reduce stress concentration and improve the plastic working of alloys; Step 5: Place the combined blank body into a muffle furnace and heat it from 400 °C to 750 °C at a heating rate of 7 °C per minute, and hold for 45 min; Step 6: Place the combined blank body heated in Step 5 into the tapered die for hot extrusion process. The hot extrusion temperature is 750 °C, and the extruded combined blank is quenched to obtain an extruded sample; The extrusion process parameters are determined according to the following method: Conduct a hot simulation compression experiment on lead-tin bronze alloy at an experimental temperature of 600 °C - 800 °C and a strain rate of 0.01 - 10. Based on the obtained stress-strain curves, establish the Arrhenius model and the Arvaim model. Combine the geometric model and boundary conditions, i.e., the heat transfer coefficient of the environment is 50 w / m²·k and the friction ratio factor is 0.4, to establish an extrusion finite element model. Study the processes with extrusion temperatures in the range of 600 °C - 800 °C, extrusion speeds of 0.01 - 10, and extrusion ratios of 4:1, 9:1, and 16:1 respectively, to obtain the strain distribution law, temperature distribution law, and recrystallized volume fraction distribution law. The optimal extrusion parameters are determined as: extrusion temperature 750 °C, extrusion ratio 9:1, and extrusion speed 10 mm / s; Step 7: Solution-treat the extruded sample in Step 6. Keep the extruded sample at 650 °C for 2 h and air-cool it to room temperature to obtain high-quality lead-tin bronze bars that meet the standards. The test results show that the tensile strength of the alloy after solution treatment reaches 446.5 MPa and the elongation reaches 29.2%, fully meeting the performance standards specified in the Specification for Copper Alloy Permanent Mold Castings for Aviation, HB - 2002 of the People's Republic of China's aviation industry standard: tensile strength greater than 238 MPa and elongation greater than 5%.
[0026] Example 3, A method for preparing a high-strength and high-toughness lead-tin bronze bar according to the present invention includes the following steps: Step 1: Heat an alloy containing 2.3% lead, 7.79% tin, 4.0% nickel, and the remaining component being copper by weight percentage to a liquid state, pour it into a water-cooled copper mold and turn on the water-cooling cycle, and take it out after cooling to obtain a cast rod-shaped lead-tin bronze alloy; Step 2: Use electrolytic purple copper with a purity of 99.9% for machining to produce a copper sleeve with a blind hole having a bottom thickness of 20 mm and an inner diameter of 45 mm. Machine the as-cast rod-shaped lead-tin bronze alloy obtained in the previous step to a diameter of 45 mm and assemble it into the blind hole of the copper sleeve. Perform vacuum sealing welding on the open end of the blind hole of the assembled copper sleeve to form an integral combined blank body; Step 3: After annealing the combined blank body at 300 °C for 25 min and applying a glass lubricant, air-cool it to 50 °C; The annealing temperature can preferably be 300 °C. The purpose is to regulate the tissue composition of the lead-tin bronze, ensure the extrusion quality, increase the proportion of the (α + β) / β phase by pre-treating the lead-tin bronze at 300 °C, and at the same time regulate the distribution of lead particles in the lead-tin bronze to ensure that the lead particles are evenly dispersed in the matrix in a spherical shape, ensuring the quality of the subsequent processed products; The purpose of applying the glass lubricant is to reduce the heat generated by friction, thereby preventing the local temperature from being too high during extrusion and reducing the deterioration of material properties caused by overheating. It ensures the surface quality of the hot-extruded products, and in a high-temperature environment, metal materials are prone to oxidation reactions. The lubricant can act as an isolation layer to reduce the contact between the metal and air and prevent the oxidation phenomenon on the material surface; Step 4: Perform a preheating treatment on a tapered die with a taper of 67°, a depth of 35 mm, and a diameter of 20 mm at 400 °C for a preheating duration of 1 h, and spray a cubic boron nitride release agent spray; Compared with flat-mouth extrusion, tapered extrusion can significantly reduce stress concentration and improve the processing plasticity of the alloy; Step 5: Place the combined blank body in a muffle furnace and heat it from 400 °C to 750 °C at a heating rate of 7 °C per minute and hold for 45 min; Step 6: Place the combined blank body heated in Step 5 in the tapered die for a hot extrusion process. The hot extrusion temperature is 750 °C, and perform a quenching treatment on the extruded combined blank to obtain an extruded sample; The extrusion process parameters are determined according to the following method: Conduct a hot simulation compression experiment on the lead-tin bronze alloy at an experimental temperature of 600 °C - 800 °C and a strain rate of 0.01 - 10. Based on the obtained stress-strain curve, establish the Arrhenius model and the Arvaim model. Combine the geometric model and boundary conditions, that is, the heat transfer coefficient of the environment is 50 w / m²·k and the friction ratio factor is 0.4, to establish an extrusion finite element model. Study the processes with an extrusion temperature range of 600 °C - 800 °C, an extrusion speed of 0.01 - 10, and extrusion ratios of 4:1, 9:1, and 16:1 respectively, obtain the strain distribution law, temperature distribution law, and recrystallized volume fraction distribution law, and determine the optimal extrusion parameters as: extrusion temperature 750 °C, extrusion ratio 9:1, and extrusion speed 10 mm / s; Step 7: Solution treatment is carried out on the extruded sample in Step 6. The extruded sample is heated at 750 °C for 2 h and then air-cooled to room temperature to obtain high-quality lead-tin bronze bars meeting the standards. The test results show that the tensile strength of the alloy after solution treatment reaches 464.4 MPa and the elongation reaches 67.1%, fully meeting the performance standards specified in the "Specification for Copper Alloy Permanent Mold Castings for Aviation" of the Aviation Industry Standard HB-2002 of the People's Republic of China: the tensile strength is greater than 238 MPa and the elongation is greater than 5%.
[0027] Example 4. A method for preparing a high-strength and high-toughness lead-tin bronze bar according to the present invention includes the following steps: Step 1: According to the weight percentage, an alloy of 2% lead, 11% tin, 4.0% nickel, and the remaining component being copper is heated to a liquid state, then poured into a water-cooled copper mold and the water-cooling cycle is started. After cooling, it is taken out to obtain a as-cast rod-shaped lead-tin bronze alloy; Step 2: Electrolytic purple copper with a purity of 99.9% is machined to produce a copper jacket with a blind hole having a bottom thickness of 20 mm and an inner diameter of 45 mm. The as-cast rod-shaped lead-tin bronze alloy obtained in the previous step is machined to a diameter of 45 mm and assembled in the blind hole of the copper jacket. The open end of the blind hole of the assembled copper jacket is subjected to vacuum sealing welding treatment to form an integral combined blank body; Step 3: The combined blank body is annealed at 270 °C for 35 min and then coated with a glass lubricant, and then air-cooled to 50 °C; Step 4: A tapered die with a taper of 70°, a depth of 30 mm, and a diameter of 20 mm is preheated at 380 °C for 1 h, and a cubic boron nitride release agent spray is sprayed; Step 5: The combined blank body is placed in a muffle furnace and heated from 350 °C to 600 °C at a heating rate of 5 °C per minute and held for 45 min; Step 6: The heated combined blank body in Step 5 is placed in the tapered die for hot extrusion process. The hot extrusion temperature is 650 °C, and the extruded combined blank is quenched to obtain an extruded sample; Step 7: The extruded sample in Step 6 is subjected to electro-pulse treatment. Specifically, the voltage of the electro-pulse is set to 50 V, the treatment time is 40 s, and the frequency is 500 Hz. After the electro-pulse treatment is completed, it is cooled to room temperature to obtain high-quality lead-tin bronze bars meeting the standards. The test results show that the tensile strength of the alloy after electro-pulse treatment is increased by more than 30% compared with the as-cast alloy, and the elongation exceeds 25%, fully meeting the performance standards specified in the "Specification for Copper Alloy Permanent Mold Castings for Aviation" of the Aviation Industry Standard HB-2002 of the People's Republic of China: the tensile strength is greater than 238 MPa and the elongation is greater than 5%.
[0028] Example 5. A preparation method of a high-strength and high-toughness lead-tin bronze rod according to the present invention includes the following steps: Step 1: According to the weight percentage, an alloy containing 3.25% lead, 7% tin, 3% nickel, and the remaining component being copper is heated to a liquid state, then poured into a water-cooled copper mold and the water-cooling cycle is started. After cooling, it is taken out to obtain a as-cast rod-shaped lead-tin bronze alloy. Step 2: Electrolytic tough pitch copper with a purity of 99.9% is machined to produce a copper sleeve with a blind hole having a bottom thickness of 20 mm and an inner diameter of 45 mm. The as-cast rod-shaped lead-tin bronze alloy obtained in the previous step is machined to a diameter of 45 mm and assembled in the blind hole of the copper sleeve. The open end of the blind hole of the assembled copper sleeve is subjected to vacuum sealing welding treatment to form an integral combined blank body. Step 3: The combined blank body is annealed at 330 °C for 25 min and coated with a glass lubricant, and then air-cooled to 100 °C. Step 4: A taper die with a taper of 67°, a depth of 35 mm, and a diameter of 20 mm is preheated at 400 °C for 0.5 h, and a cubic boron nitride release agent spray is sprayed. Step 5: The combined blank body is placed in a muffle furnace and heated from 400 °C to 800 °C at a heating rate of 10 °C per minute and held for 30 min. Step 6: The heated combined blank body in Step 5 is placed in the taper die for hot extrusion process. The hot extrusion temperature is 800 °C, and the extruded combined blank is quenched to obtain an extruded sample. Step 7: The extruded sample in Step 6 is subjected to solution treatment. The extruded sample is held at 750 °C for 1 h and then air-cooled to room temperature to obtain a high-quality lead-tin bronze rod meeting the standards. The test results show that the tensile strength of the alloy after solution treatment is increased by more than 35% compared with the as-cast alloy, and the elongation exceeds 30%, fully meeting the performance standards specified in the Specification for Metal Mold Castings of Copper Alloys for Aviation, HB - 2002 of the People's Republic of China: the tensile strength is greater than 238 MPa and the elongation is greater than 5%.
[0029] The results of Examples 1 - 5 show that the method combining preheating treatment and extrusion with a taper sleeve can inhibit the hot brittleness during the hot extrusion of lead-tin bronze, successfully realize the extrusion forming of lead-tin bronze alloy, and the surface quality of the rod is good without forming defects such as microcracks.
[0030] Figure 1 Shown is the schematic diagram of the as-cast structure of the alloy in Example 1, which is a typical dendritic morphology, with coarse structure and severe segregation between dendrites. Figure 2 Shown is the schematic diagram of the microstructure of the extruded sample in Example 2. It can be seen from the figure that after hot extrusion, the dendrites are broken, obtaining a fine equiaxed crystal morphology, with fine and uniform structure and obvious improvement in segregation.Figure 3 It is a schematic diagram of the microstructure after electro-pulse treatment in Example 1. As can be seen from the figure, the distribution of the microstructure after electro-pulse treatment is fine and uniform, which is beneficial to improving the mechanical properties of the alloy; Figure 4 It is a schematic diagram of the microstructure of the extruded sample in Example 2 after solution treatment. As can be seen from the figure, after solution treatment, the tin-rich phase dissolves back, and the grains tend to grow.
[0031] After electro-pulse treatment, the pulsed lead-tin bronze alloy bars are obtained. After solution treatment, the solutionized lead-tin bronze alloy bars are obtained. After hot extrusion, the dendritic crystals are transformed into fine equiaxed crystals through recrystallization. Under the action of pulsed treatment or solution treatment, the tin-rich phase in the equiaxed grains dissolves back, and the lead particles are redistributed, and the tissue distribution is more uniform, significantly improving the mechanical properties of the alloy, fully meeting the performance standards specified in the Specification for Metal Mold Castings of Copper Alloys for Aviation HB-2002 of the People's Republic of China's aviation industry.
Claims
1. A method for preparing high-strength and toughness lead-tin bronze rods, characterized in that: The following steps are involved: Step 1: Heat a metal material containing 2.0%-3.25% lead, 7.0%-11.0% tin, 3.0%-4.0% nickel and the rest copper to a liquid state according to weight percentage, pour the metal material into a water-cooled copper mold and start a water-cooling cycle, and take the mold out after cooling to obtain a cast lead-tin bronze alloy; Step 2: Electrolytic copper with a purity of 99.9% is machined to produce a copper sheath with a blind hole, and the cast lead-tin bronze obtained in the previous step is assembled into the blind hole on the copper sheath, and the blind hole opening end of the assembled copper sheath is sealed to form an integral combined blank body; Step 3: After the assembled combined blank body is annealed at 270°C-330°C for 25min-35min and coated with glass lubricant, it is air-cooled to 50°C-100°C; Step 4: Preheat the cone-mouth extrusion die with a taper of 67°-70°, a depth of 30mm-35mm, and a diameter of 20mm at 380°C-400°C for 0.5h-1h. After preheating, spray the die with cubic boron nitride release agent spray; Step 5: Place the combined green body into a muffle furnace, heat it from 350°C-400°C to 600°C-800°C at a heating rate of 5°C-10°C per minute, and keep it warm for 30min-45min; Step 6: placing the combined blank body heated in step 5 in a tapered die for hot extrusion at a temperature of 650° C. to 800° C., and quenching the combined blank body after extrusion to obtain an extruded sample; Step 7: Heat treat the extruded sample obtained in step 6 to obtain high-quality lead-tin bronze rods that meet the standards.
2. The method for preparing a high-strength and toughness lead-tin bronze rod according to claim 1, characterized in that: The extrusion ratio of the hot extrusion process is 9:1, and the extrusion speed is 5 mm / s-10 mm / s.
3. The method for preparing a high-strength and toughness lead-tin bronze rod according to claim 1, characterized in that: The extruded sample was subjected to heat treatment, which was electric pulse treatment. The voltage of the electric pulse was set to 50V-100V, the treatment time was 35s-40s, the frequency range was 350Hz-500Hz, and it was cooled to room temperature after the electric pulse treatment was completed.
4. The method for preparing a high-strength and toughness lead-tin bronze rod according to claim 1, characterized in that: The extruded samples were subjected to a heat treatment, which was a solution treatment, in which the extruded samples were kept at 650°C-750°C for 1h-2h and then air-cooled to room temperature.
Citation Information
Patent Citations
A semi-solid reverse extrusion method for copper alloy bushing parts
CN112024843B
Hot extrusion forming method of copper alloy rail
CN112170523A
High-strength wear-resistant copper alloy and preparation method thereof
CN104164589A
High strength and high elasticity tin bronze alloy and solid solution process thereof
CN107604203A
Preparation method of high-strength tin bronze alloy
CN114262854A